Effects of exogenous auxin on yield in foxtail millet (Setaria italica L.) when applied at the grain-filling stage - Feng, Zhiwei; Zhao, Jing; Nie, Mengen; Qu, Fei; Li, Xin; Wang, Juanling (Frontiers in Plant Science, 2023)
The objective of this experiment was to explore the effects of the synthetic auxin naphthalene acetic acid (NAA) on the physiological processes of foxtail millet, and to provide a theoretical basis and technical approaches for its efficient use in millet cultivation. Two foxtail millet varieties (‘Jingu 21’ and ‘Zhangzagu 5’) were treated with six concentrations of NAA from 0-144 mg L-1 at the grain-filling stage in field experiments. The photosynthetic pigment contents, gas exchange parameters, chlorophyll fluorescence parameters, and grain yield were measured in foxtail millet. The results showed that low concentrations of NAA (18-36 mg L-1) increased the contents of photosynthetic pigments, and increased the activities of antioxidant enzymes, the photosynthetic rate, and the activity of photosystem system II (PS II). At higher NAA concentrations, the facilitation effect of the treatments diminished, showing a clear concentration effect. In this study, yield was significantly and positively correlated with PS II effective quantum yield (Y(II)) and the PSII electron transport rate (ETR), and the net photosynthetic rate (Pn) was significantly and positively correlated with chlorophyll content, stomatal conductance (Gs), Y(II), and ETR. These results also indicated that exogenous NAA application promotes the production of ATP and NADPH by increasing the efficiency of electron transfer within the photosystems and also improved photochemical utilization, which facilitates the fixation and reduction of carbon, ultimately leading to an increase in Pn and increasing grain yield in foxtail millet.